Process risk and reliability management : operational integrity management - Sutton, Ian (William Andrew Publishing, 2010)
Helps executives, managers and technical professionals achieve their process safety management (PSM) goals, as well as to make the transition to an operational integrity strategy. This book focuses on the energy and process industries - from refineries, to pipelines, chemical plants, transportation, alternative energy and offshore facilities